2022
DOI: 10.1111/1346-8138.16672
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cutaneous manifestations in COVID‐19: A meta‐analysis

Abstract: The global epidemic of coronavirus disease 2019 (COVID‐19) endangers more and more people. Many studies on cutaneous manifestations related to COVID‐19 have emerged, but their prevalence has varied widely. The objective of this study was to conduct a meta‐analysis estimating the prevalence of skin manifestations in COVID‐19. Four databases PubMed, Web of Science, CBM, and CNKI were searched, and the results were screened by two reviewers. A random‐effects model was used to evaluate the overall prevalence. Hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…While there are several studies that have reported a significant difference in age, duration, and VASI score between patients with vitiligo+COVID-19 and those with vitiligo only, there are also studies that have reported conflicting results. For example, a study by Li et al found no significant difference in age, duration, or VASI score between COVID-19 patients with vitiligo and those without vitiligo [ 23 ]. Similarly, a study by Christensen et al reported no significant difference in the prevalence of vitiligo between COVID-19 patients and the general population [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…While there are several studies that have reported a significant difference in age, duration, and VASI score between patients with vitiligo+COVID-19 and those with vitiligo only, there are also studies that have reported conflicting results. For example, a study by Li et al found no significant difference in age, duration, or VASI score between COVID-19 patients with vitiligo and those without vitiligo [ 23 ]. Similarly, a study by Christensen et al reported no significant difference in the prevalence of vitiligo between COVID-19 patients and the general population [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cutaneous lesions associated with SARS-CoV-2 infection are commonly observed in clinical practice, with their prevalence estimated to be around 6% [ 12 ]. Although no formal classification has yet been established, the cutaneous manifestations associated with SARS-CoV-2 infection can generally be categorised into six groups (Table 2 ) [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [34] in their MA estimated a pooled prevalence of cutaneous manifestations of 5.6% (95% CI: 0.040-0.076), with the prevalence of detailed types as follows: maculopapular rash 2%, livedoid lesions 1.4%, petechial lesions 1.1%, urticaria 0.8%, pernio-like lesions 0.5%, vesicular lesions 0.3%.…”
Section: Frequency Of Signsmentioning
confidence: 99%